Socio-demographic factors associated with low birth weight in a tertiary care hospital of Odisha - Bhue, Pradip Kumar; Acharya, Himansu Prasad; Pradhan, Subrat Kumar; Biswal, Pratima; Swain, Amit Pritam; Satapathy, Durga Madhab (International Journal Of Community Medicine And Public Health, 2018)
Background: World Health Organization has defined low birth weight (LBW) as birth weight less than 2,500 grams. Giving birth to a LBW infant is influenced by several factors. Objective of the study was to measure the proportion of low birth weight babies delivered in V.S.S medical college and hospital, Burla and its association with socio-demographic factors. Methods: Hospital based cross -sectional study comprising of 1030 postnatal women who delivered single live baby in V.S.S Medical College and Hospital, Burla. Selection of study participants was done by systematic random sampling in the study period October 2012 to September 2014. Chi-square test was used to measure association between LBW and socio-demographic factors. Results: The proportion of LBW was found to be 27.76%. The proportion of LBW babies was high and significant in extremes of age i.e. teenage (44.19%) and 30 years and above age group (39.56%) and Muslim mothers (36.36%), illiterate mothers (53.52 %), manual labourer (67.14%), socioeconomic class IV and V (32.98%), consanguinity history (60.58%), smoky fuel (30.02%), consumption of tobacco (49.11%). Conclusions: The proportion of LBW (27.76%) was found to be higher than national average (21.5%).